2021
DOI: 10.1111/acps.13385
|View full text |Cite
|
Sign up to set email alerts
|

Functional and cognitive impairment in the first episode of depression: A systematic review

Abstract: Objectives: To describe the cognitive and functional impairment in individuals with the first episode of major depressive disorder (MDD) as compared to controls and individuals with recurrent MDD. Also to describe the functional and cognitive trajectory after the first episode of MDD.Methods: A total of 52 studies were included in our systematic review. 32 studies compared the cognitive performance between first episode of depression (FED) and controls, 11 studies compared the cognitive performance between rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 87 publications
1
34
0
1
Order By: Relevance
“…Furthermore, concerning cognition, impaired processing speed was significant associated with more difficulties in performing ADL 16. Finally, a similar pattern has been observed among patients with UD 17–19…”
Section: Introductionsupporting
confidence: 75%
“…Furthermore, concerning cognition, impaired processing speed was significant associated with more difficulties in performing ADL 16. Finally, a similar pattern has been observed among patients with UD 17–19…”
Section: Introductionsupporting
confidence: 75%
“…A possible explanation may be the high prevalence of PTSD: PTSD is characterized, among other symptoms, by poor cognitive flexibility, processing speed, controlled and sustained attention, higher response inhibition, and recall memory ( Schultebraucks et al, 2022 ), all traits observed in our cohort. On the other hand, processing speed and executive/working memory are the most commonly impaired domains in depression ( Varghese et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the classification criteria of the 10th revision of the International Statistical Classification of Diseases and Related Health Problems, MDD is classified into the first depressive episode (FDE) and recurrent depressive episodes (RDE) ( Yuksel et al, 2018 ). Previous studies have demonstrated differences in depressive and somatic symptoms ( Roca et al, 2011 ), cognitive functioning ( Roca et al, 2015 ; Zu et al, 2021 ; Varghese et al, 2022 ), and quality of life ( Zu et al, 2021 ) between patients with RDE and those with FDE. Epidemiological surveys have shown that depression has a high recurrence rate and that, once the first episode has occurred, it relapses within 5 years.…”
Section: Introductionmentioning
confidence: 99%